Studi Kelayakan Bisnis Pengembangan Pemasaran PT. Rizki Prima Food - Iqlima Octavianidori; Muhamad Nazar Fadilah; Sadiah Permata Sari; Doni Ramdani; M. Randi Rukmana; Darsiti Darsiti; Meilani Purwanti (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2024)
Marketing Expansion at PT. Rizki Prima Food is the main focus of development in conducting a feasibility study for this business. The method used in this business feasibility study is field research. This research uses primary data and also secondary data. Creating an e-commerce account on Shopee to expand marketing from PT. Rizki Prima Food itself is one solution to increase turnover and petekres is increasingly known to the wider community. With quite a lot of achievements, and also complete supporting certificates, it will make it easier for PT. Rizki Prima Food made its product a best seller.